Nutrients Requirements and Composition in A Grouper Fish Feed Formulation - Soong, Cai-Juan; Ramli, Razamin; Abdul Rahman, Rosshairy (Future Academy, 2016)
Due to the high nutrients and desirable taste, there is a high demand of grouper fish. However, the supply of wild catch grouper fish is limited and insufficient to meet the cyclical nature of high demand in grouper fish consumption leading to the high price. Consequently, grouper fish is worth to be farmed due to its high value price and high market demand. In order to farm grouper fish, there is a need to have a lot of trash fish, but trash fish is expensive, hard to store, hard to maintain the quality of nutrient and quantity throughout the years. Thus, there is a need to formulate the fish feed based on the nutrients requirements with an extensive survey of literature. Results show that grouper fish need crude protein 40-45%, crude fat 1-10%, crude fibre 0.5-8%, moisture 0.8-95.5%, ash 0.4-18%, phosphorus 0.1-1.8% , calcium 2-4%, and essential acid amino (EAA).This important information can be considered in further study in formulating fish feed to minimize cost and maximize profit in farming grouper fish